REGULASI DIRI MEMEDIASI PENGARUH RESILIENSI DAN LINGKUNGAN KELUARGA TERHADAP HASIL BELAJAR (Survey pada Siswa Kelas XI IPS SMA Negeri se-Kabupaten Cianjur pada Mata Pelajaran Ekonomi) - Risa Cahya Maulani Falencya Galizty, - (2022)
This research is based by the low learning outcomes of students in economic subjects in SMA Negeri in Cianjur Regency. The purpose of this study was to determine and analyze self-regulated learning mediating the effect of resilience and family environment on student learning outcomes. The method used in this research is an explanatory survey with data collection techniques through questionnaires and observations. The population of this study was all students of class XI IPS SMA Negeri in Cianjur Regency and obtained a sample of 223 students with simple random sampling technique. The data that has been collected is then analyzed using multiple linear regression analysis with mediator variables. The results showed that: (i) resilience and family environment were in the high category, while self-regulated learning and learning outcomes were in the medium category. (ii) resilience affects self-regulated learning. (iii) family environment influences self-regulated learning. (iv) resilience has an effect on learning outcomes. (v) family environment influences learning outcomes. (vi) self-regulated learning affects learning outcomes. (vii) resilience affects learning outcomes either directly or indirectly through self-regulated learning. (viii) family environment influences learning outcomes either directly or indirectly through self-regulated learning. The results of this study indicate that the concepts of resilience, family environment, and self-regulated learning, are relevant and can estimate student learning outcomes. Keywords: Resilience, Family Environment, Self-Regulated Learning, Learning Outcomes